GE_GERICHTE P/5261/2019 vom 13. Januar 2020 - GE Cour de justice (2020)
CLASSEMENT DE LA PROCÉDURE;QUALITÉ POUR AGIR ET RECOURIR;INFRACTIONS CONTRE L'HONNEUR;SITE INTERNET | CPP.382; CPP.104; CPP.118; CPP.115; CP.3; CP.8